Tujuan Tujuan Pendidikan Islam Berbasis MabÄdi â€™Khaira Ummah - Herman Wicaksono (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2020)
Education objective is one of inseparable parts of education implementation, including Islamic education. The absence of concrete and measurable objectives of Islamic Education is one of the reasons why this study is conducted. This study aims to provide new breakthrough in the case of Islamic education objectives based on the concept of MabÄdi 'Khaira Ummah. This kind of concept is a principle used in the social field triggered by one of Islamic organizations in Indonesia, NU, which is considered relevant to be used as a reference in formulating the objectives of Islamic education. This study belongs to qualitative approach and library research method. The data were collected by collecting some related references. The collected data then analyzed to be formulated into objectives of Islamic Education. As a result, this study provides a conclusion that the objective of Islamic education is creating honest, trustworthy, honorable, fair, helpful, as well as generous students.